2008
DOI: 10.1055/s-2008-1081292
|View full text |Cite
|
Sign up to set email alerts
|

Converging Effects ofGinkgo bilobaExtract at the Level of Transmitter Release, NMDA and Sodium Currents and Dendritic Spikes

Abstract: In this study, an attempt was made to integrate the effects of GINKGO BILOBA extract (GBE) in different experimental systems (IN VITRO cochlea, brain slice preparations and cortical cell culture) to elucidate whether these processes converge to promote neuroprotection or interfere with normal neural function. GBE increased the release of dopamine in the cochlea. NMDA-evoked currents were dose-dependently inhibited by rapid GBE application in cultured cortical cells. GBE moderately inhibited Na+ channels at dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Several studies have indicated that G. biloba extracts may affect the brain dopamine system and dopamine-mediated functions (Shah et al, 2003;Szasz et al, 2008;Yeh et al, 2008;Fehske et al, 2009). However, this is the first report linking the effects of EGb 761 to the PFC, that is, the brain area that is neuroanatomically relevant to learning and memory processing.…”
Section: T Yoshitake Et Almentioning
confidence: 79%
See 1 more Smart Citation
“…Several studies have indicated that G. biloba extracts may affect the brain dopamine system and dopamine-mediated functions (Shah et al, 2003;Szasz et al, 2008;Yeh et al, 2008;Fehske et al, 2009). However, this is the first report linking the effects of EGb 761 to the PFC, that is, the brain area that is neuroanatomically relevant to learning and memory processing.…”
Section: T Yoshitake Et Almentioning
confidence: 79%
“…Several studies have indicated that G. biloba extracts may affect the brain dopamine system and dopamine‐mediated functions (Shah et al. , 2003; Szasz et al. , 2008; Yeh et al.…”
Section: Discussionmentioning
confidence: 99%
“…EGb761 was also shown to reduce neuronal death in global brain ischemia and Glu‐induced excitotoxicity (Chandrasekaran et al. 2002), and inhibit NMDA receptor‐mediated calcium influx and neuronal death (Szasz et al. 2008; Shi et al.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of EGb761 were shown in in vitro injury models induced by hypoxia, hydrogen peroxide, glutamate, verapamil, Aβ and nitric oxide (NO) [52] , as well as in an in vivo model induced by ischemia [53,54] . The purported biological effects of EGb761 include amelioration of mitochondrial dysfunction [55] , blockade of the NMDA receptor [56,57] , scavenging of free radicals, lowering of oxidative stress, reduction of neural damages, reduction of platelet aggregation, antiinflammation [58] and anti-aging [59] . Clinically, EGb761 has been prescribed to treat central nervous system (CNS) disorders such as AD and cognitive deficits, which may be attributed to the aforementioned effects.…”
Section: Ginkgo Biloba Linnmentioning
confidence: 99%